2021
DOI: 10.1038/s42003-021-02189-9
|View full text |Cite
|
Sign up to set email alerts
|

Claudin-2 promotes colorectal cancer liver metastasis and is a biomarker of the replacement type growth pattern

Abstract: Claudin-2 promotes breast cancer liver metastasis by enabling seeding and early cancer cell survival. We now demonstrate that Claudin-2 is functionally required for colorectal cancer liver metastasis and that Claudin-2 expression in primary colorectal cancers is associated with poor overall and liver metastasis-free survival. We have examined the role of Claudin-2, and other claudin family members, as potential prognostic biomarkers of the desmoplastic and replacement histopathological growth pattern associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 76 publications
0
44
0
Order By: Relevance
“…Subsequent experiments further confirmed this result ( Figure 5 ), supporting that COX5B is positively correlated with CLDN2 expression in CRCs. CLDN2 is a promising tight junction localized protein with well-characterized functions, including promoting the tumorigenicity, metastasis, and susceptibility of cells to 5-FU, perhaps through ameliorating cancer stem cell property in CRCs [ 36 , 37 , 38 ]. Our findings partially reflect that CLDN2 acts as an effector downstream of COX5B-induced control of cell proliferation and sensitivity to anticancer drugs ( Figure 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent experiments further confirmed this result ( Figure 5 ), supporting that COX5B is positively correlated with CLDN2 expression in CRCs. CLDN2 is a promising tight junction localized protein with well-characterized functions, including promoting the tumorigenicity, metastasis, and susceptibility of cells to 5-FU, perhaps through ameliorating cancer stem cell property in CRCs [ 36 , 37 , 38 ]. Our findings partially reflect that CLDN2 acts as an effector downstream of COX5B-induced control of cell proliferation and sensitivity to anticancer drugs ( Figure 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…The outer proteins were all membrane proteins, and include the three tetraspanins used for capture (CD9, CD63, CD81) as well as CD82, another tetraspanin and known tumor metastasis suppressor; 52 and the integrin (ITG) subunits (α2, α6, β1, β4) 8 that have been associated with EV-mediated metastatic organotropism. 8 Among the inner proteins was the tight junction protein claudin-2, 53 a prognosis biomarker of replacement-type liver metastasis in EVs from CRC patients, 54 detected through its cytoplasmic domain, and cytosolic proteins, which were selected based on known and widespread association with EVs. 55 They included the heat-shock proteins (HSP90, HSP70), 56 and ESCRT-associated protein Alix, which is involved in EV biogenesis and cargo sorting.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to UPR activation, RNA-Seq analysis revealed that the most common significantly downregulated genes were associated with cancer cell proliferation and invasiveness. For example, CLDN2 expression was recently linked to increased incidence of CRC-associated liver metastasis [165], whereas CXCR4 [63] and CYP24A1 [64] are increasingly recognized as prognostic markers for CRC progression. PIF1 downregulation is usually associated with decreased survival in neoplastic cells, but not in nonmalignant cells [60], whereas PSRC1 has been confirmed to be involved in microsatellite instability (MSI)-a genetic condition resulting from incompetent DNA mismatch repair, and frequently associated with CRC incidence and progression [166].…”
Section: Discussionmentioning
confidence: 99%